Electrochemical characterisation and sensing of diclofenac anion and dibucaine cation by ion transfer across water and dichlorohexane interface - Abdulla, Eissa Mohammed Almbrok (2021)
Ion sensing is a significant challenge in both clinical diagnosis and environmental monitoring. Ion transfer reactions at liquid | liquid interfaces allow detection of substances that are not easy to oxidise/reduce or that undergo significant interference in these reactions. In addition, it offers the advantages of simplicity of instrumentation, easily of miniaturisation and portability. However, very few sensing applications have been reported for the quantitative analysis of organic molecules, including drugs. This study discussed the characterisation, and application of ion transfer at the interface between two immiscible electrolyte solutions (ITIES) using cyclic voltammetry (CV) and differential pulse voltammetry (DPV). Early studies have relied on the exploration of the electrochemical behaviour of diclofenac anion (DCF-) and dibucaine cation (DIC+) via water|1,6-dichlorohexane (1,6-DCH) at such regular ITIES and in particular examination of the pH of the aqueous phase. Both ions were found to undergo ion-transfer voltammetry at the liquid | liquid interface. Some of the analytical parameters, such as standard transfer potential, the Gibbs energy of transfer and the partition coefficient, for DCF- and DIC+ were determined. Subsequently, essential modifications to the ITIES by micropores silicon nitride membrane were brought to enhance the analytical performance and lower the detection limits. The micro-ITIES array formed with 2500 micropores arranged in a cubic close-packed (CCP) arrangement, with a diameter of 2.5±0.09 μm, a pore centre-to-centre separation of 12.65±0.13 μm and 100 nm membrane thickness, was electrochemically characterised by ion transfer of the model analyte, tetramethylammonium cation (TMA+), across the water | 1,6-DCH interface. The resulting voltammogram has showed the linear diffusion dominance within the arrays, suppressing the radial diffusion at the edge of the arrays, due to overlapping diffusion profiles at adjacent micro-ITIES resulted in lower experimental current. The analytical performance of micro- ITIES to drug molecules (DCF- and DIC+) detection in the aqueous phase was investigated, with the limits of detection (LODs) in the ranges of 8–56 μM and 4–24 μM were calculated to be 1.5±0.05 μM and 0.9±0.06 μM for DCF- and DIC+, respectively. In addition, the influence of possible interfering substances (ascorbic acid, sugar, amino acid, urea, and metal ions) on the detection of DCF- and DIC+ was investigated. Finally, the ability to use electrochemistry at liquid | liquid micro-interface for direct determination of the targeted drugs in bio-mimic fluids (serum and saliva) and in a realistic mixture (human urine) were assessed. Both drugs could be detected in biological matrices, despite of deproteinisation of samples is required for detecting DCF in artificial serum. The LODs were 12.9±.5 μM and 1.4±0.02 μM in artificial serum, 1.8±0.2 μM and 1.5±0.14 μM in artificial saliva and 2.6±0.2 μM and 1.2±0.12 μM in human urine sample for DCF- and DIC+, respectively.